Spine metastases: are minimally invasive surgical techniques living up to the hype?. (July 2015) - Zairi, Fahed; Vieillard, Marie-Helene; Assaker, Richard
SUMMARY : Surgery is still considered the mainstay treatment of spine metastases. However, conventional surgery is associated with a high complication rate that may delay the initiation of adjuvant therapies and make some patients not eligible. Minimally invasive surgical techniques have been developed to overcome these drawbacks while providing the same benefits than standard open surgery. In recent years, there has been a flourishing enthusiasm demonstrating the advantages of these various techniques. Although, it is clear that these techniques have greatly improved the treatment of spine metastases, each has its own limitations. In this report, we list the main minimally invasive surgical techniques emphasizing their advantages and drawbacks.